Analysis of the microtensile bond strength to enamel of two adhesive systems polymerized by halogen light or LED - Carvalho,Ana Paula Morales Cobra (2005)
With the development of composite resin polymerization techniques, LEDs were introduced to the market place. Based on the studied literature, the aim of this study was to evaluate, through microtensile testing, the bond strength to enamel of a composite resin associated to a conventional (multi-bottle) adhesive system or to a self etching primer adhesive system, polymerized by halogen light or LED (light emitting diode). Bovine teeth were divided into 4 groups with 10 teeth each (n = 10). Then the adhesives Scotchbond Multipurpose Plus (3M-ESPE) and Clearfil SE Bond (Kuraray) were applied following the manufacturers instructions. Both systems were polymerized for 10 s by halogen light (Degulux Soft Start - Degussa Hulls) set at 550 mW/cm² or by LED (Kerr Demetron) set at 600 mW/cm². The composite resin Filtek Z-250 was applied in four 1 mm increments with the aid of a square, condensation silicon, 5 mm x 5 mm matrix, and polymerized by either of light sources for 40 s. Scotchbond Multipurpose Plus polymerized by halogen light presented the highest bond strength values (39.69 ± 7.07 MPa), and the other groups did not present statistically significant differences: Scotchbond Multipurpose Plus polymerized by LED (22.28 ± 2.63 MPa), Clearfil SE Bond polymerized by halogen light (27.82 ± 2.65 MPa) and by LED (22.89 ± 5.09 MPa).